Random anion distribution in MSxSe2−x (M = Mo, W) crystals and nanosheets. Issue 18 (9th March 2018) - Nguyen, Minh An T.; Gupta, Arnab Sen; Shevrin, Jacob; Akamatsu, Hirofumi; Xu, Pengtao; Lin, Zhong; Wang, Ke; Zhu, Jun; Gopalan, Venkatraman; Terrones, Mauricio; Mallouk, Thomas E.
Abstract : Nanosheets exfoliated from single crystals of the group VIb sulfoselenides (MS x Se2− x, M = Mo, W) are solid solutions at the atomic level. Abstract : The group VIb dichalcogenides (MX2, M = Mo, W; X= S, Se) have a layered molybdenite structure in which M atoms are coordinated by a trigonal prism of X atoms. Ternary solid solutions of MS x Se2− x were synthesized, microcrystals were grown by chemical vapor transport, and their morphologies and structures were characterized by using synchrotron X-ray diffraction, Rietveld refinement, DIFFaX simulation of structural disorder, scanning electron microscopy, and energy dispersive X-ray spectroscopy. Double aberration corrected scanning transmission electron microscopy was used to determine the anion distributions in single-layer nanosheets exfoliated from the microcrystals. These experiments indicate that the size difference between S and Se atoms does not result in phase separation, consistent with earlier studies of MX2 monolayer sheets grown by chemical vapor deposition. However, stacking faults occur in microcrystals along the layering axis, particularly in sulfur-rich compositions of MS x Se2− x solid solutions.